Química mineral e condições de cristalização do granito Gradaús, sul do Pará, Província Carajás. - NERY, Paulo Hiago de Souza (Universidade Federal do Pará, 2020)
The Gradaús Granite (1882±9 Ma) is part of the intense anorogenic granitic magmatism that occurred during the paleoproterozoic in Carajás Province. It has a rounded shape, with about 800 km² of outcrop area, and is intrusive in metassediments of the Rio Fresco Group. It is composed of five petrographic facies with varying mafic content and texture. The amphiboles are calcic, predominantly Fe-edenites with Fet/(Fet+Mg) ratios between 0.77 and 0.9; hastingsites and Fe-hornblendes occurs subordinately. Biotite is ferrous, with compositions close to the annite pole, with Fet/(Fet+Mg) ratios between 0.81 and 0.96. Based on the aluminum content in the amphibole the emplacement pressure of the pluton was estimated at 240 e 360 MPa. Temperature estimates obtained from the zirconium saturation geothermometer, interpreted as close to the beginning of crystallization, ranged from 780 to 870 °C, while those near the solidus obtained from the amphibole geothermometer ranged from 700 to 750 °C. Amphiboles with high Fet/(Fet+Mg) ratios, the presence of ilmenite> magnetite and the absence of magmatic titanite indicate that Gradaús pluton crystallized under reduced conditions, probably between NNO and FMQ buffers. Biotites show alkaline-subalkaline compositions and always plot in A-type granite fields. Comparative data on mineral chemistry and crystallization conditions with other anorogenic granites from Carajás Province indicate, according to recent studies, that Gradaús Granite has greater similarities to the Serra dos Carajás Suite granites.